Customary Offenses and Their Sanctions in Indonesia: Analysis of Bengkulu City Regional Regulation No. 29 of 2003 and Rejang Lebong Regency Regional Regulation No. 5 of 2018 - Andiko, Toha; Khairuddin, Khairuddin (Madania: Jurnal Kajian Keislaman, 2024)
This research aims to describe the advantages and disadvantages of customary regulations in the city of Bengkulu and Rejang Lebong district, as well as to provide alternative solutions for the improvement of customary regulations so that they are not overlapping with higher regulations and can be deeper in absorbing the laws that live in society, without neglecting justice, expediency, and legal certainty applicable in Indonesia. This research is included in the form of normative juridical research. This type of research is qualitative. The approach used in this research is a statutory approach (statue approach). As a result, the implementation of customary law in Bengkulu city with regard to customary violations has gone quite well, for example in the case of Cempalo Tangan in the form of stealing or damaging (article 21 of Bengkulu City Regional Regulation No. 29 of 2003). Whereas in Rejang Lebong, it has also worked well, for example in other serious cempalo cases such as killing (article 25 of Rejang Lebong Regency Perda No.5 of 2018). In the review of Islamic law, sanctions for customary violations that occur in Bengkulu city are generally not contrary to Islamic law, and are in line with the principle of zawajir. In the review of positive law in Indonesia, the punishment for thieves with customary fines in the form of apologies, compensation, and performing the traditional ceremony of tepung Setawar Sedingin, this is contrary to article 362 which stipulates a maximum prison sentence of 5 years, and if accompanied by violence/threats, shall be sentenced to a maximum imprisonment of 9 years (Article 365 of the Indonesian Penal Code). Penelitian ini bertujuan untuk mendeskripsikan kelebihan dan kekurangan yang ada pada Perda Adat di kota bengkulu dan kabupaten Rejang Lebong, sekaligus memberikan solusi alternatif untuk perbaikan Perda Adat tersebut agar tidak overlapping dengan peraturan yang lebih tinggi dan bisa lebih dalam menyerap hukum yang hidup dalam masyarakat, tanpa mengabaikan keadilan, kemanfaatan, dan kepastian hukum yang berlaku di Indonesia. Penelitian ini termasuk dalam bentuk penelitian yuridis normatif. Jenis penelitian ini adalah kualitatif. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan perundang-undangan (statue approach). Hasilnya, implementasi hukum adat di kota Bengkulu yang berkenaan dengan pelanggaran adat sudah berjalan cukup baik, contohnya dalam kasus Cempalo Tangan berupa mencilok (mencuri) atau merusak (pasal 21 Perda Kota Bengkulu No. 29 Tahun 2003). Sedangkan di Rejang Lebong, sudah juga berjalan baik contohnya pada kasus cempalo berat lainnya seperti membunuh (pasal 25 Perda Kabupaten Rejang Lebong No.5 Tahun 2018). Dalam tinjauan hukum Islam, sanksi terhadap pelanggaran adat yang terjadi di kota Bengkulu secara umum tidak bertentangan dengan hukum Islam, dan sejalan dengan prinsip zawajir. Dalam tinjauan hukum positif di Indonesia, hukuman bagi pencuri dengan denda adat berupa permohonan maaf, ganti kerugian, dan melakukan upacara adat tepung setawar sedingin, ini bertentangan dengan pasal 362 yang menetapkan hukuman penjara selama-lamanya 5 tahun, dan jika disertai kekerasan/ ancaman, dihukum penjara selama-lamanya 9 tahun (Pasal 365 KUHP)